Genetic organization of the cSOD microregion of Drosophila melanogaster. - Staveley, B.E.; Hilliker, A.J.; Phillips, J.P. (Genome, 1991)
Cu/Zn superoxide dismutase (cSOD) is an important enzymatic agent of physiological defense against active oxygen species. Previously, we defined the essential biological role of cSOD in Drosophila through analysis of a cSOD null mutant. In the process of isolating this mutant, we also identified several vital genes in the chromosomal region surrounding the cSOD gene (the cSOD microregion). To further our genetic analysis of cSOD function, we have undertaken a detailed description of the cSOD microregion as defined by the breakpoints of the deficiency Df(3L)lxd9. Examination and correlation of mutations previously recovered with new X-ray induced mutations described in this paper identify a total of 12 vital genes, including cSOD, and one nonvital gene, lxd, in this region. We propose the adoption of a single genetic nomenclature for the genes of this region. Two newly generated hypomorphic alleles of cSOD are described that confer phenotypes similar to cSODn108, confirming the important physiological role of the enzyme in Drosophila.